Domain-specific concussion knowledge and reporting in United States Major League Rugby players - Stamm, J. M.; Hunzinger, K. J.; Sheehy, O. M.; Baugh, C. M. (European Journal of Sport Science, 2026)
Previous research indicates high concussion knowledge is not associated with better concussion reporting, with research examining the relationship between reporting and global concussion knowledge. Concussion knowledge has not yet been investigated in United States Major League Rugby (MLR) players. This study evaluated domain-specific concussion knowledge, concussion history, and reporting behaviors among active MLR players. In a cross-sectional design, 207 MLR athletes (age 26.6 ± 3.4 years) completed a survey assessing concussion history, knowledge, and nondisclosure reasons. While in the MLR, 24% reported an undisclosed concussion, with nondisclosure reasons related to a lack of concussion knowledge, a desire to continue playing, or not wanting to let the coach and/or team down. Significant positive correlations between concussion knowledge statements indicated three concussion knowledge domains: Immediate Management, Potential Post-Concussion Consequences, and Concussion Recognition. MLR players demonstrated the least knowledge in the Concussion Recognition domain and the greatest knowledge in the Potential Post-Concussion Consequences domain. Athletes with more reported concussions (across measures) or ding/bell rung instances were more likely to correctly disagree with false statements about concussions (rs range -0.153 to rs = -0.371), particularly in the concussion recognition domain. Understanding gaps in specific concussion knowledge domains and how those gaps influence concussion reporting could inform more targeted concussion education and potentially improve concussion reporting where nondisclosure is due to concussion knowledge misconceptions. Future research should explore domain-specific concussion knowledge in diverse athletic populations.